MELAS Syndrome with Cardiac Involvement: A Multimodality Imaging Approach - Sara Seitun; Laura Massobrio; Anna Rubegni; Claudia Nesti; Margherita Castiglione Morelli; Sara Boccalini; Athena Galletto Pregliasco; Irilda Budaj; Luca Deferrari; Gian Marco Rosa; Fabrizio Montecucco; Alberto Valbusa (Case Reports in Cardiology)
A 49-year-old man presented with chest pain, dyspnea, and lactic acidosis. Left ventricular hypertrophy and myocardial fibrosis were detected. The sequencing of mitochondrial genome (mtDNA) revealed the presence of A to G mtDNA point mutation at position 3243 (m.3243A>G) in tRNALeu(UUR) gene. Diagnosis of cardiac involvement in a patient with Mitochondrial Encephalomyopathy, Lactic Acidosis, and Stroke-like episodes syndrome (MELAS) was made. Due to increased risk of sudden cardiac death, cardioverter defibrillator was implanted.